Body balance at static posturography in vestibular migraine - Gorski,Leslie Palma (2019)
Abstract Introduction: Migraine is one of the most frequent and incapacitating headaches, with a high degree of impairment in quality of life. Its association with vestibular symptoms is common, including imbalance and postural instability. Objective: To evaluate the body balance of patients with vestibular migraine through a static posturography test. Methods: An experimental group of 31 patients with a medical diagnosis of vestibular migraine in the intercritical period of the disease, and a control group of 31 healthy individuals, matched for age and gender, were submitted to the eight sensory conditions of the Tetrax Interactive Balance System. The parameters analyzed were: stability index, which measures the amount of sway, global stability and ability to compensate postural modifications; weight distribution index, which compares deviations in weight distribution; synchronization index, which measures the symmetry in the weight distribution; postural sway frequency, which indicates the frequency range with more sway; and fall risk index, which expresses the probability of falls. Results: The stability index was higher in the experimental group in all eight sensory conditions, with a significant difference between the groups in six of them. The weight distribution index was higher in the experimental group in all conditions, with a significant difference in three of them. The number of cases with preferential sway in F2-F4 was significantly higher in the experimental group in three conditions, and in F5-F6 in two, while the fall risk was significantly higher in the experimental group than in the control group. Conclusion: Patients with vestibular migraine showed compromised body balance at the static posturography test.